Childhood sarcoidosis: a case report - Anh, Le Thy Phuong; Mao, Nguyen Van; Yen, Hoang Thi Thuy (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Childhood sarcoidosis is a rare multisystemic granulomatous disorder of unknown etiology. The diagnosis is often delayed due to lacking of recognition of clinical features. We report a 23 month-old boy who presented with multiple pinkish papules and painless cystic swellings in his ankles and wrists. A skin biopsy showed multiple sarcoidal granulomatous lesions. He was treated with steroids and had a good response. Childhood sarcoidosis is characterized by arthritis, uveitis, and cutaneous involvement. Glucocorticoids remain the first choice therapy for children with multisystem involvement. The prognosis of early-onset childhood sarcoidosis varies in different studies due to the rarity of the disease. Keywords: Childhood sarcoidosis, granulomatous disorder, arthritis, uveitis